(untitled) (Scientific Journal of Research Studies in Future Psychology, 2024)
The aim of this study was to investigate the relationship between teachers 'creativity and virtual education continuance intention of students with the mediating role of the family environment. The present research is an applied one in terms of purpose and a correlational study in terms of method. The research population consisted of all students and teachers of Chalus schools during the academic year 2021-2022 which among them, 60 teachers and 240 students were selected as a sample. The tools of this research included the Rendsip's Creativity Questionnaire (1979), the E-Learning continuance intention Questionnaire of Bhattacherjee et al. (2006), and the Family Environment Questionnaire of Sanaei. The collected data were analyzed using structural equation modeling, SPSS 24, and LISREL 8.8 software. The results showed that teachers 'creativity and family environment have a direct and significant effect on virtual education continuance intention of students (p <0.05). The results of model fit indices also showed that the family environment can mediate the relationship between teachers 'creativity and virtual education continuance intention of students (p <0.05). These results showed that virtual education continuance intention of students is largely determined by the creativity of teachers and their living and family environment. Therefore, the reassuring communication of families plays an important role in the development of the child's educational goals. Also, presenting innovative and creative methods of teacher in training affects students' learning.